Experimental study of bank runs in the context of loss aversion - Dohnal, Ondřej; Chytilová, Helena; Cingl, Lubomír, 1984-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2019)
This thesis examines whether loss aversion, used as a motivator on tested subjects, has any impact on the number of withdrawals in the context of bank runs game with presence of sunspots. In order to verify our hypotheses, we conducted an experiment based on modified payoff function built upon fundamentals of D&D model in light of Arifovic and Jiang (2015). This experiment takes form of simultaneous game where subjects make a binary choice whether to withdraw money from the bank in the first or in the second round under corresponding fee, which represents a partial loss of their deposits. The main treatment variable is coordination parameter (η) defined as the minimum fraction of depositors required to wait so that waiting entails a higher payoff than withdrawing. We conduct treatments with three levels of coordination parameter (0,2; 0,7 and 0,9), which differ with respect to strategic uncertainty and level of risk. Results suggest that loss aversion enhances optimal behavior in treatment with great strategic uncertainty in a sense of lower probability of a bank run.
Vedoucí práce: Helena Chytilová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses